Confidence, Pessimism and their Impact on Product Differentiation in a Hotelling Model with Demand Location Uncertainty - Florian Kauffeldt; Boris Wiesenfarth (University of Heidelberg, Department of Economics, 2014)
We analyze a Hotelling location-then-price duopoly game under demand uncertainty with uniformly distributed consumers in a standard quadratic costs scenario. The novelty of our approach consists of assuming that firms' beliefs are represented by non-extreme-outcome-additive (neo-additive) capacities. We derive firms' subgame-perfect product design decisions under ambiguity. Furthermore, we investigate the influence of ambiguity and ambiguity attitude on equilibrium product differentiation and contrast our results with an environment of risky firms. We find that the impact of the degree of confidence or ambiguity is particularly significant when it comes to delivering accurate explanations for a wide range of phenomena related to observed product design behavior.
urn:nbn:de:bsz:16-heidok-167726
Keywords: 330; Hotelling; Confidence; Optimism; Pessimism; Degree of Ambiguity; Choquet Expected Utility; Neo-additive Capacities; Product Differentiation